+0  
 
0
46
1
avatar

I'm quite confused as to how I should tackle this

 Feb 19, 2020
 #1
avatar+109740 
+1

f(x)    =  x^3 * x^(-2) * x ^(1/2)  =  x ^(3 - 2 + 1/2)  =  x ^( 1 + 1/2)  =  x^(3/2)

 

 

 l(x)    = 3x^2  [  2  - x^(-1) ]  + 3x   - (2x)^2

 

           =  6x^2  -  3x^2*x^(-1)  + 3x   - 4x^2

 

            =  6x^2  - 3x  + 3x  -  4x^2

 

             =  2x^2

 

                               x √x                                         x * x^(1/2) * x^(3)

 h(x)  =            __________________    =             ______________   =

                         (x^(-1))^(-2)  * x^(-3)                              x^2 

 

 

                                           x^ (1 + 1/2 + 3)              x ^(4 + 1/2)

                                         ______________  =      ___________  =   x^(4 + 1/2 - 2)  =

                                                      x^2                         x^2

 

                                                 x^(2 + 1/2)  = 

 

                                                   x^(5/2)

 

 

                  x^5  *  x^ (5/4)                x^5  * x^(5/4)            x^5 * x^(5/4)

k(x)   =     _____________  =           ____________  =   ____________   =   x^5

                     √ [x^(5/2)]                    (x^(5/2)(^(1/2)            x^(5/4)

 

 

 

cool cool cool

 Feb 19, 2020

46 Online Users

avatar
avatar
avatar